Direct-developing frogs: ontogeny of Oreobates barituensis (Anura: Terrarana) and the development of a novel trait - Goldberg, Francisco Javier (2012)
Within Anura, direct development involves ontogenetic changes of the biphasic ancestral pattern. The recent partitioning of the genus Eleutherodactylus, along with the proposition of the unranked taxon Terrarana, has renewed an interest to the morphological and ecological diversity among direct-developing frogs. The morphological changes during embryonic development of Oreobates barituensis is similar to those of other Neotropical direct-developing species, including the reduction or absence of several larval and embryonic characters (e.g., external gills and adhesive glands), heterochronic changes (e.g., early developing limbs and late persistence of ciliated epidermal cells), and the appearance of new structures (e.g., egg tooth). The tail achieves an extraordinary peramorphic development (encloses the entire embryo), and the location of its expanded part is interpreted as a heterotopic change resulting in a novel trait. An enveloping tail with apparently non-heterotopic fins, combined with the absence of gills, has been only reported for a species of the related genus Craugastor, and these morphologies suggest an informative perspective for the study of evolution of direct development in terraranans.